STRENGTHENING QUR’ANIC ECOLOGICAL ETHICS INTO COMMUNITY-BASED WASTE MANAGEMENT IN GALUGA VILLAGE - Hana Natasya; Hidayatul Hikmah; Jazillatul Rizkiana; Jihan Fauziah; Khairunnisa; Lisnawati (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2026)
This community service initiative aims to transform community behavior through the integration of Qur’anic ecological ethics into community-based waste management. Using the Asset-Based Community Development (ABCD) method, this program identifies spiritual values as the primary asset to drive resident participation. The results of the community service initiative demonstrate that internalizing the concept of Khalifah fil Ard and the prohibition against fasad (corruption) in Surah Al-Baqarah: 30 and Surah Al-A’raf: 56 has successfully increased residents’ awareness regarding waste sorting and the creation of biopores. Technically, biopores successfully reduced household organic waste and improved soil permeability. This community service project concluded that strengthening religious literacy combined with simple technology is effective in achieving environmental sustainability in areas facing an ecological crisis.